GRADUATE EMPLOYABILITY OUTCOMES OF TRANSNATIONAL DOUBLE DEGREE PROGRAMS: PATHWAYS TO GLOBAL LABOR MARKET INTEGRATION - Sadullaeva Zukhra Oybek kizi (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Transnational double degree programs have become an important mechanism for preparing competitive graduates for the global labor market. This article analyzes the impact of such programs on graduate employability, focusing on competency development, international academic mobility, and labor market integration. The study highlights how joint curricula, international accreditation, and cross-cultural learning environments enhance graduates’ professional readiness. The findings demonstrate that double degree programs significantly increase employment opportunities, global career mobility, and the acquisition of transferable skills required in the modern knowledge economy.